Improving risk communication (National Academy Press, 1989)
Hazards of modern life surround us and so, too, does communication about the risks of those hazards. News reports describe such hazards as pollutants in the air and in drinking water, pesticide residues in food, threats from radiation and toxic chemicals, and AIDS. Government and industry also send out messages about hazards and their risks, sometimes directly to the populace but more often through intermediaries, such as the print and broadcast media. Risk messages are difficult to formulate in ways that are accurate, clear, and not misleading. This report addresses these and other problems confronting risk communication.